2022
DOI: 10.1002/iid3.700
|View full text |Cite
|
Sign up to set email alerts
|

Sinomenine pretreatment alleviates hepatic ischemia/reperfusion injury through activating Nrf‐2/HO‐1 pathway

Abstract: Introduction Ischemia–reperfusion (IR) injury is induced by an interrupted blood flow and succeeding blood restoration, which is common in the operation of liver transplantation. Serious IR injury is a major reason leading to transplant failure. Hepatic IR is featured by excessive inflammatory response, oxidative stress, and apoptosis. Sinomenine (SIN) is derived from the herb Sinomeniumacutum and shows properties of anti‐inflammation and antiapoptosis in multiple IR‐induced organ injuries. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The dose of SIN was selected based on several previously published studies. 17 , 21 Rats in group I and II were injected with normal sterile saline at the same frequency. Rats received daily i.p.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The dose of SIN was selected based on several previously published studies. 17 , 21 Rats in group I and II were injected with normal sterile saline at the same frequency. Rats received daily i.p.…”
Section: Methodsmentioning
confidence: 99%
“…Hepatic I/R was induced based on a previous research. 17 In brief, hepatic ischemia was created by using a microvascular clip and lasted for 1 h, as confirmed by the pale appearance of the clamped lobes. The clip was then discreetly displaced to permit a 3‐h blood reperfusion.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Z.G. Yang et al reported that SIN inhibited oxidative stress and inflammatory responses by promoting Nrf-2/HO-1 signaling activation, thereby ameliorating inflammation by increasing TNF-α, IL-6, and IL-8 and decreasing IL-10 [ 208 ]. Y. Li et al demonstrated the protective effect of SH on liver injury induced by Pb.…”
Section: Organs Protectionmentioning
confidence: 99%